Pengaruh Transformasi Digital Dan Pelatihan Kerja Terhadap Kinerja Pegawai Dengan Kepuasan Kerja Sebagai Variabel Intervening Pada Instansi BPKPAD Kabupaten Pesisir Selatan - A Ide Triyosa; Vicky Brama Kumbara; Chintya Ones Charli (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2026)
This study aims to analyze the effect of digital transformation and job training on employee performance with job satisfaction as an intervening variable at the Badan Pengelolaan Keuangan dan Aset Daerah Kabupaten Pesisir Selatan. The research used a quantitative approach with a survey design. The population consisted of all 64 employees, and the sampling technique used was total sampling (census). Data were collected through questionnaires using a Likert scale. The data analysis method employed Structural Equation Modeling (SEM) based on Partial Least Square (PLS). The results indicate that digital transformation has a significant effect on employee performance. Job training has a significant effect on job satisfaction but does not significantly affect employee performance. Digital transformation does not significantly affect job satisfaction. Job satisfaction also does not have a significant effect on employee performance. Indirectly, job training and digital transformation do not have a significant effect on performance through job satisfaction as an intervening variable. These findings imply that employee performance improvement is more strongly influenced by the direct implementation of digital transformation than by job satisfaction mediation.